MENINGIOMAS OF THE CEREBELLAR TENTORIUM: THE RESULTS OF SURGICAL TREATMENT - V. V. Stupak; I. S. Kopylov; I. V. Pendyurin; S. V. Tsvetovskiy; D. A. Dolzhenko; A. V. Novokshonov; T. M. Shogunbekov (Сибирский научный медицинский журнал, 2019)
Aim of the study was to evaluate the surgeries of tentorial meningiomas in Neurosurgical Department No.1 of the Novosibirsk Institute of Traumatology and Orthopedics. Material and methods. Study includes 64 patients with tentorial meningiomas of different location, treated surgically from 2008 to 2017. Among them 55 (85.9 %) were female patients and 9 were male (14.1 %) with average age of 62.9 years in females and 56.7 years in males. For diagnostic purposes, the patients were performed brain magnetic resonance imaging and/or computed tomography with or without contrast agents. In this series, 83 % of the tumors were of large or giant (with diameter of more than 4 cm). In 63 cases the tumors were typical meningiomas and only 1 case was a malignant anaplastic meningioma. Results. All patients were treated surgically in one or two steps. Overall, there were 70 standard microsurgical resections. Electromyography with Neuropack-2 («NIHON KOHDEN Corp.», Japan) was performed to control brain stem function during the surgery, with short latency auditory evoked potentials (SLAEPs) received. When sinus walls were affected, the tumor matrix was processed with 20W neodymium laser in coherent mode and ablation. In 63 cases, gross-total resection was achieved: Simpson I (76.6 %, n = 49) and Simpson II (21.8 %, n = 14). One patient (1.6 %) was treated with subtotal resection because of complicated surgical approach and massive transverse sinus and sinus confluence bleeding. Post-operative mortality was 3.1 % (2 cases). SLAEP data did not demonstrate any significant irritation or damage to the brain stem with performed surgical approaches. There were no infections of the surgical wound, meninges, brain or CSF leaks after the surgery. Discussion. Tentorial meningiomas are rare brain tumors treated with gross-total tumor resection when possible. Performed surgeries resulted in mild functional decrease in quality of life, but Karnofsky scale for each patient was returning to its original state in 2 weeks. Complications, including neurological disability, presented in 19 % (n = 12) of the patients, and post-operative mortality did not exceed the common literature data. Most of the focal neurological disabilities have disappeared in 2 weeks after the surgery.